Satuan Lingual Yang Mengandung Pronomina Persona Pertama Pada Teks Terjemahan Al Quran - Erlinawati, Mira, Prof. Dr. Markhamah, M.Hum, Prof. Dr. Abdul Ngalim, M.M, M.Hum (2014)
The research has three purpose 1 To assess and determine the linguistic hierarchy containing pronoun Persona First on the Koran Subtitle. 2 To analyze filled function containing pronoun Persona First on the Koran Subtitle. 3 To determine the role of containing the pronoun Persona First the Koran Subtitle. Object of this research is the use of lingual units containing pronominal persona on TTA. Data collection method used is the method refer to. Refer to the method is a method of data collection is done by listening to the language use of the object under study. In addition to the methods used as well consider the documentary method. Data collection techniques used in this study include the techniques involved freely refer note capably and techniques. Techniques used to listen to the text refer to the translation of the Quran (TTA) to identify the data on the various units using persona lingual containing pronouns 1 note technique used to record data units using persona lingual containing pronouns contained in the text of the Quran translation (TTA). Data analysis techniques with a unified method and method agih. The results of this study: (1) The hierarchy of linguistic form of words and phrases. Lingual unit that includes the noun form of the word. Berpronomina lingual unit that includes the phrase persona FN, Enkliti, F Prep, FV, F Atr, F Adj (2) Function containing pronouns first persona on translation of the Quran text is filler function subject, predicate, object, complement, statement (3) roles containing pronouns first persona subtitles Koran include the role of actors, actions/deeds, direction/goals, described or classified, explanatory, recipient, location, patient, objective, acquiring, known, designated, passive action, time, experince, patients. Conclusions This study lingual unit containing the PP I in TTA are various categories, functions and roles